Anti-aging Effects of Alu Antisense RNA on Human Fibroblast Senescence Through the MEK-ERK Pathway Mediated by KIF15 - Ji, Ning; Wu, Chong-guang; Wang, Xiao-die; Song, Zhi-xue; Wu, Pei-yuan; Liu, Xin; Feng, Xu; Zhang, Xiang-mei; Wang, Xiu-fang; Lv, Zhan-jun (Current medical science, 2023)
Objective To investigate whether human short interspersed nuclear element antisense RNA (Alu antisense RNA; Alu asRNA) could delay human fibroblast senescence and explore the underlying mechanisms. Methods We transfected Alu asRNA into senescent human fibroblasts and used cell counting kit-8 (CCK-8), reactive oxygen species (ROS), and senescence-associated beta-galactosidase (SA-β-gal) staining methods to analyze the anti-aging effects of Alu asRNA on the fibroblasts. We also used an RNA-sequencing (RNA-seq) method to investigate the Alu asRNA-specific mechanisms of anti-aging. We examined the effects of KIF15 on the anti-aging role induced by Alu asRNA. We also investigated the mechanisms underlying a KIF15-induced proliferation of senescent human fibroblasts. Results The CCK-8, ROS and SA-β-gal results showed that Alu asRNA could delay fibroblast aging. RNA-seq showed 183 differentially expressed genes (DEGs) in Alu asRNA transfected fibroblasts compared with fibroblasts transfected with the calcium phosphate transfection (CPT) reagent. The KEGG analysis showed that the cell cycle pathway was significantly enriched in the DEGs in fibroblasts transfected with Alu asRNA compared with fibroblasts transfected with the CPT reagent. Notably, Alu asRNA promoted the KIF15 expression and activated the MEK-ERK signaling pathway. Conclusion Our results suggest that Alu asRNA could promote senescent fibroblast proliferation via activation of the KIF15-mediated MEK-ERK signaling pathway.